Analysis Of Students' Writing Abilities in Recount Text For Morphological And Syntactical Errors - Pramadanti, Rindika (Program Studi Pendidikan Bahasa Inggris Kabupaten Kepulauan Aru, 2023)
This study aims to identify morphological and syntactic errors and the frequency, type and causes students to make when writing essays in recount texts. Qualitative research is the research methodology used. The papers of thirty first-semester ASA Indonesia University students in East Jakarta were used as data sources. Students must write an essay in English as part of the data collection process. Students can choose any theme they want to write in their paper. Based on the information discovered, 59 errors fell into the Morphology category, and 113 errors fell into the Syntax category of 172 errors detected. This research demonstrates that excessive generalization, intralingual variables, and interlingual factors contribute to students' writing difficulties. Therefore, students' poor writing abilities show that grammar is flawed in essay writing, particularly in experiential literature.